The Influence of Entrepreneurial Orientation and Customer Relationship Management on MSME Competitiveness - Sembiring, Lenny Dermawan; Setyawati, Amelia; Indajang, Kevin; Putri, Juan Anastasia; Sudirman, Acai (IJBLE Scientific Publications Community Inc., 2023)
Competitive advantage is realized through continuous sustainability (sustainable competitive advantages), so new strategies must be designed. The strategy designed will certainly be able to dominate both the old market and the new market. The main aim of this research is to analyze the influence of entrepreneurial orientation and customer relationship management on MSME competitiveness. This research uses a literature and field design with a causal associative approach. This study uses a research instrument test consisting of validity and reliability tests. The quantitative analysis consists of a normality test, regression test, hypothesis test, correlation test, and coefficient of determination. Data analysis confirms that entrepreneurial orientation and customer relationship management have a significant effect on MSME competitiveness. The implications of research on entrepreneurial orientation and Customer Relationship Management (CRM) on business competitiveness can provide valuable insights for Micro, Small, and Medium Enterprises (MSME) owners and related parties. Research on entrepreneurial orientation and CRM can help MSMEs develop more targeted business strategies. They can understand how innovation and customer relationship management can be key drivers of their business competitiveness.